EFEKTIVITAS KOMBINASI ANTIPSIKOTIK DENGAN LORAZEPAM PADA PASIEN SKIZOFRENIA: SEBUAH TINJAUAN NARATIF - Karina Aulia Firdasya; Woro Harjaningsih; Fivy Kurniawati (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
ABSTRACT Schizophrenia is a chronic psychiatric disorder characterized by psychotic symptoms that require prompt and effective management. Antipsychotic medications are the mainstay of treatment; however, under certain clinical conditions, they are combined with lorazepam to improve the management of acute agitation. This narrative review aimed to synthesize the available scientific evidence regarding the effectiveness of antipsychotic–lorazepam combination therapy in patients with schizophrenia. A literature search was conducted using Scopus, PubMed, ScienceDirect, and Google Scholar. English-language articles published between 2015 and 2025 were selected based on predefined inclusion and exclusion criteria and were analyzed narratively. Of the 2,092 articles identified, twelve studies met the eligibility criteria. The findings indicated that antipsychotic–lorazepam combination therapy effectively reduced acute agitation and psychotic symptoms, as assessed using the Positive and Negative Syndrome Scale (PANSS), Positive and Negative Syndrome Scale Excited Component (PANSS-EC), Brief Psychiatric Rating Scale (BPRS), Clinical Global Impression (CGI), and Agitation-Calmness Evaluation Scale (ACES). Risperidone–lorazepam demonstrated efficacy comparable to conventional intramuscular therapy with a lower risk of extrapyramidal symptoms, while haloperidol–lorazepam showed efficacy comparable to intramuscular olanzapine. Overall, the available evidence suggests that antipsychotic–lorazepam combination therapy may represent an effective treatment option with an acceptable safety profile for managing psychosis and acute agitation in patients with schizophrenia. ABSTRAK Skizofrenia merupakan gangguan kejiwaan kronis yang ditandai oleh gejala psikosis sehingga memerlukan penanganan yang cepat dan efektif. Antipsikotik merupakan terapi utama, namun pada kondisi tertentu dikombinasikan dengan lorazepam untuk membantu mengendalikan agitasi akut. Tinjauan naratif ini bertujuan mensintesis bukti ilmiah mengenai efektivitas kombinasi antipsikotik dan lorazepam pada pasien skizofrenia. Penelusuran literatur dilakukan melalui Scopus, PubMed, ScienceDirect, dan Google Scholar. Artikel berbahasa Inggris yang diterbitkan pada periode 2015–2025 diseleksi berdasarkan kriteria inklusi dan eksklusi, kemudian dianalisis secara naratif. Dari 2.092 artikel yang teridentifikasi, dua belas penelitian memenuhi kriteria. Hasil telaah menunjukkan bahwa kombinasi antipsikotik dengan lorazepam efektif menurunkan agitasi dan gejala psikosis akut berdasarkan pengukuran menggunakan Positive and Negative Syndrome Scale (PANSS), Positive and Negative Syndrome Scale Excited Component (PANSS-EC), Clinical Global Impression (CGI), dan Agitation-Calmness Evaluation Scale (ACES). Kombinasi risperidone-lorazepam memberikan efektivitas yang sebanding dengan terapi intramuskular konvensional dengan risiko gejala ekstrapiramidal yang lebih rendah, sedangkan kombinasi haloperidol-lorazepam menunjukkan efektivitas yang sebanding dengan olanzapine intramuskular. Secara keseluruhan, kombinasi antipsikotik dan lorazepam berpotensi menjadi pilihan terapi yang efektif dengan profil keamanan yang secara umum dapat diterima pada penatalaksanaan psikosis dan agitasi akut pasien skizofrenia.